Inclusion in Elementary Schools - Galis, Susan Allan; Tanner, C. Kenneth (Education Policy Analysis Archives, 1995)
This study of reform policy focused on inclusive education in the 1990s in the state of Georgia, United States of America. Program modifications including, individualizing instructional methods, adapting the instructional environment, and lowering maximum class size emerged as significant issues. We found that policies related to these areas were compounded by the less experienced educators not readily accepting change strategies for serving students. Apparently younger educators are engrossed in surviving daily routine and have difficulty coping with the complex demands of change. Regular education teachers have difficulty with the idea of inclusion. Legal aspects dealing inclusion need clarification, especially for regular education teachers.